Epidemiological aspects of astrovirus and coronavirus in poults in the South Eastern Region of Brazil - Silva,S.E.L. da (2009)
A survey of Turkey Coronavirus (TCoV) and Astrovirus (TAstV-2) prevalence was carried out from February to December during 2006 year in semiarid region of Brazil, from a turkey producer area, localized in South Eastern of Brazil. To asses the risk factor related to clinical material, climatic condition and type of RT-PCR applied, cloacal swabs (CS), faeces, sera, bursa of Fabricius (BF), thymus (TH) and spleen (SP) and ileum-caeca region were collected from 30-day-old poults suffering of enteritis episode characterized as poult enteritis mortality syndrome (PEMS). The PEMS clinical features were characterized by watery to foamy faeces, light brown-yellow in colour and low mortality rate. Meteorological data (rainfall and relative humidity) observed during along the study presented monthly average temperature ranging from 39.3 and 31.2ºC, precipitation in rainy season from 40 to 270.3 mm/month, and no rain during dry season. Simplex RT-PCR gave odds ratio (OR) values suggesting that ileum-caeca region is at higher chance (OR=1.9; p=0.9741) to have both viral RNA than faeces (OR=1.5; p=0.7319). However, multiplex RT-PCR showed 3.98 (p=0.89982) more chance to give positive results in faeces than CS at dry season. The major risk factors seem to be low rate of humidity and high temperatures at winter, probably responsible for spread, easily, the TCoV and TAstv-2 among the flocks. The positive results of both virus suggested that they can play an important role in enteric disorders, associated to low humidity and high temperatures frequently found in tropical countries.